Wiki as a Tool for Engaging Students with a Science Problem Solving Activity - Freire, Sofia (2013)
This study aims at knowing how students experience wikis while they are involved in a problem solving science activity. The study took place in a physics and chemistry 8th grade class (13 years old), where teacher implemented a problem solving activity about acid-base reactions, using a wiki. Participants were 20 students, of which 12 were female students. The activity involved six different working groups. Wikis were analyzed with the goal to identify students’ level and quality of participation. Furthermore, in order to understand students’ experiences concerning the learning situation six focus group interviews were carried on. Three highly participating groups presented successful strategies and achieved the learning goals. These students used complex strategies for analyzing the information and used theoretical knowledge to make sense of information gathered. The collaborative processes were essential for enabling a feeling of competence and for assuring a successful learning experience. These groups revealed a high level of cognitive engagement. In comparison, poorly participating groups didn’t present a successful strategy of knowledge co-construction and revealed difficulties in understanding the scientific concepts involved. Furthermore, each poorly participating group experienced the learning situation quite differently. Results suggest that students’ engagement with a problem solving activity using a wiki is affected by a complex interplay of emotional, technical and social issues. Some recommendations for facilitating students’ engagement with wikis emerge from the study: to carefully support collaborative processes and to create safe learning environments in which error is valued as an opportunity for learning.